2014
DOI: 10.1002/gcc.22157
|View full text |Cite
|
Sign up to set email alerts
|

The effect of UGT1A and UGT2B polymorphisms on colorectal cancer risk: Haplotype associations and gene–environment interactions

Abstract: UDP-glucuronosyltransferases (UGTs) play an important role in the phase II metabolism of exogenous and endogenous compounds. As colorectal cancer (CRC) etiology is thought to involve the biotransformation of dietary factors, UGT polymorphisms may affect CRC risk by altering levels of exposure. Genotyping of over 1800 Caucasian subjects was completed to identify the role of genetic variation in nine UGT1A and five UGT2B genes on CRC risk. Unconditional logistic regression and haplotype analyses were conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…25 In line with a protective effect conferred by this allele, a second study found an interaction between a haplotype comprising the intergenic marker rs7586006 tightly linked to rs11563250 and frequent NSAID use that significantly decreased colorectal cancer risk. 26 …”
Section: Discussionmentioning
confidence: 99%
“…25 In line with a protective effect conferred by this allele, a second study found an interaction between a haplotype comprising the intergenic marker rs7586006 tightly linked to rs11563250 and frequent NSAID use that significantly decreased colorectal cancer risk. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Although the overall rate of BA glucuronidation is low in comparison with tauro- and glyco-conjugation, it represents a major form in the urinal and fecal elimination of BAs since BA glucuronides do not undergo enterohepatic circulation [ 30 ]. Moreover, UDP-glucuronosyltransferases that catalyze BA glucuronidation are susceptible to regulation by various pathophysiological factors [ 31 , 32 ]; therefore, it is important to monitor BA glucuronides in the pathological conditions for the intensive understanding of BA dysregulation patterns. To facilitate the process of simultaneous quantification of 28 BAs including the glucuronidation products, a method based on a UFLC-Triple-TOF/MS system was developed and validated.…”
Section: Resultsmentioning
confidence: 99%
“…studies with retrospective collection of data on NSAID use (case–control studies). In total, eight prospective and 21 case–control studies were identified. Tables and S1 show results on interactions between NSAID use and polymorphisms in relation to CRC from prospective and case–control studies respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the search strategy. A new search (May 2014) identified no new studies in PubMed and one case–control study in Embase which was included in Table …”
Section: Methodsmentioning
confidence: 99%